Higher order chromatin structures in maize and Arabidopsis. - Paul, A L (1998)
We are investigating the nature of plant genome domain organization by using DNase I- and topoisomerase II-mediated cleavage to produce domains reflecting higher order chromatin structures. Limited digestion of nuclei with DNase I results in the conversion of the >800 kb genomic DNA to an accumulation of fragments that represents a collection of individual domains of the genome created by preferential cleavage at super-hypersensitive regions. The median size of these fragments is approximately 45 kb in maize and approximately 25 kb in Arabidopsis. Hybridization analyses with specific gene probes revealed that individual genes occupy discrete domains within the distribution created by DNase I. The maize alcohol dehydrogenase Adh1 gene occupies a domain of 90 kb, and the maize general regulatory factor GRF1 gene occupies a domain of 100 kb in length. Arabidopsis Adh was found within two distinct domains of 8.3 and 6.1 kb, whereas an Arabidopsis GRF gene occupies a single domain of 27 kb. The domains created by topoisomerase II-mediated cleavage are identical in size to those created by DNase I. These results imply that the genome is not packaged by means of a random gathering of the genome into domains of indiscriminate length but rather that the genome is gathered into specific domains and that a gene consistently occupies a discrete physical section of the genome. Our proposed model is that these large organizational domains represent the fundamental structural loop domains created by attachment of chromatin to the nuclear matrix at loop basements. These loop domains may be distinct from the domains created by the matrix attachment regions that typically flank smaller, often functionally distinct sections of the genome.